Solid sulfide electrolyte
The LiCuPSX solid material prepared by introducing copper dopants into lithium batteries solves the problems of safety hazards of liquid electrolytes and insufficient conductivity of solid electrolytes in lithium batteries, achieving higher ionic conductivity and lower activation energy, improving improve the safety and service life of the battery.
Patent Information
- Application Number
- CN202180023833.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-23
- Filing Date
- 2021-03-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-03-18
AI Technical Summary
The liquid electrolytes used in existing lithium batteries have safety risks, and it is difficult to achieve solid electrolytes with high lithium ion conductivity in solid lithium batteries.
By introducing copper dopants, a new LiCuPSX solid material with higher ionic conductivity and lower activation energy is prepared for use as a solid electrolyte in lithium batteries.
Achieving higher ionic conductivity and lower activation energy while maintaining chemical and mechanical stability reduces the risk of lithium dendrite formation and improves battery safety and service life.
Smart Images

Figure GDA0005091380000000061 
Figure GDA0005091380000000071 
Figure GDA0005091380000000171
Abstract
Description
[0001] This application claims priority from application No. 20164967.0 filed in Europe on March 23, 2020, the entire contents of which are incorporated by reference into this application for all purposes.
[0002] The present invention relates to a process for producing a solid material according to the following general formula (I):
[0003] Li 6-x-2y Cu x PS 5-y X (I)
[0004] wherein X is a halogen, 0.005≤x≤5; and 0≤y≤0.5; the method comprises at least introducing at least lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound, optionally in one or more solvents. The present invention also relates to the solid material and its use as a solid electrolyte, especially for electrochemical devices. Background Art
[0005] Lithium batteries are used to power portable electronics and electric vehicles due to their high energy and power density. Conventional lithium batteries utilize a liquid electrolyte composed of lithium salts dissolved in an organic solvent. Since organic solvents are flammable, the aforementioned system raises safety issues. Lithium dendrites form and pass through the liquid electrolyte medium, which may cause a short circuit and generate heat, resulting in accidents leading to serious injuries. Since the electrolyte solution is a flammable liquid, when used in a battery, there are problems such as leakage and fire. In view of this problem, it is desirable to develop a solid electrolyte with a higher degree of safety as an electrolyte for the next generation of lithium batteries.
[0006] Non-flammable inorganic solid electrolytes provide a solution to the safety issue. In addition, the mechanical stability of non-flammable inorganic solid electrolytes helps to inhibit lithium dendrite formation, prevent self-discharge and heating problems, and extend the service life of the battery.
[0007] Solid sulfide electrolytes are beneficial for lithium battery applications due to their high ionic conductivity and mechanical properties. These electrolytes can be pelletized and attached to the electrode material by cold pressing, which eliminates the need for a high temperature assembly step. Eliminating the high temperature sintering step eliminates one of the challenges of using lithium metal anodes in lithium batteries. Due to the widespread use of all solid-state lithium batteries, there is an increasing demand for solid electrolytes with high lithium ion conductivity. An important class of such solid electrolytes is the argyrodite structure with a composition of Li 6 PS 5 X (X = Cl, Br) materials. Argentum has long been known and is derived from argyrodite Ag. 8 G JZ 6, which was first described by C. Winkler in 1886 and whose analysis led to the discovery of germanium. The family of argyrodite consists of more than 100 crystalline solids and includes, for example, those solid compounds in which silver is replaced by copper, germanium by gallium or phosphorus and sulfur by selenium. Thus, Nitsche, Kuhs, Krebs, Evain, Boucher, Pfitzner and Nilges described, inter alia, Cu 9 GaS 6 、Ag 7 PsE 6 and Cu 8 GaS 5 Cl compounds whose solid-state structures are derived from argyrodite.
[0008] As reported in the literature, most of the lithium argyrodite, and in particular most of the Li 6 PS 5 Cl, was prepared by dry or wet mechanochemical routes.
[0009] However, new solid sulfide electrolytes are needed with optimized properties, such as higher ionic conductivity and lower activation energy, without compromising other important characteristics like chemical and mechanical stability. Summary of the invention
[0010] Surprisingly, it has been found that, unlike the usual Li 6 PS 5 A novel solid sulfide electrolyte having higher ionic conductivity and lower activation energy than conventional lithium sulfide electrolytes can be obtained by using copper dopants. The novel LiCuPSX solid materials of the present invention also exhibit chemical and mechanical stability and processability at least similar to those of conventional lithium argyrodite. The solid materials of the present invention can also be prepared with improved productivity and allow control of the morphology of the obtained products. In addition, the solid materials of the present invention exhibit lower amounts of raw material impurities, such as Li 2 S and LiCl impurities. The solid materials of the present invention also exhibit lower amounts of undesirable phases such as γ-Li 3 PS 4 .
[0011] The present invention then relates to a solid material according to the following general formula (I):
[0012] Li 6-x-2y Cu x PS 5-y X (I)
[0013] in:
[0014] -X is selected from the group consisting of: F, Cl, I and Br;
[0015] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0016] -0≤y≤0.5, preferably 0≤y≤0.25.
[0017] The present invention also relates to a process for producing a solid material according to the following general formula (I):
[0018] Li 6-x-2y Cu x PS 5-y X (I)
[0019] in:
[0020] -X is selected from the group consisting of: F, Cl, I and Br;
[0021] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0022] -0≤y≤0.5, preferably 0≤y≤0.25;
[0023] The method comprises at least introducing at least lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound, optionally in one or more solvents.
[0024] The present invention also relates to a process for preparing a solid material according to the following general formula (I):
[0025] Li 6-x-2y Cu x PS 5-y X (I)
[0026] in:
[0027] -X is selected from the group consisting of: F, Cl, I and Br;
[0028] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0029] -0≤y≤0.5, preferably 0≤y≤0.25;
[0030] The method comprises at least the following steps:
[0031] a) obtaining a composition by mixing stoichiometric amounts of lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound, optionally in one or more solvents, under an inert atmosphere;
[0032] b) subjecting the composition obtained in step a) to a mechanical treatment;
[0033] c) optionally removing at least a portion of the one or more solvents from the composition obtained in step b) so as to obtain a solid residue;
[0034] d) heating the resulting residue obtained in step c) at a temperature ranging from 100° C. to 700° C. under an inert atmosphere, thereby forming the solid material; and
[0035] e) optionally processing the solid material obtained in step d) to a desired particle size distribution.
[0036] The invention furthermore relates to a solid material obtainable by said first process.
[0037] The solid material of the present invention can also be produced by a full solution method. Notably, the present invention also relates to a method for preparing a solid material according to the following general formula (I):
[0038] Li 6-x-2y Cu x PS 5-y X (I)
[0039] in:
[0040] -X is selected from the group consisting of: F, Cl, I and Br;
[0041] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0042] -0≤y≤0.5, preferably 0≤y≤0.25;
[0043] The method comprises at least the following steps:
[0044] a′) obtaining a solution by mixing stoichiometric amounts of a lithium compound, a sulfide compound, a phosphorus compound, a halogen compound and a copper compound in one or more solvents under an inert atmosphere;
[0045] b') removing at least a portion of the one or more solvents from the composition obtained in step a') so as to obtain a solid material; preferably at a temperature ranging from 30°C to 200°C, under an inert atmosphere;
[0046] c') heating the solid material as obtained in step b') at a temperature ranging from 100°C to 700°C, optionally under an inert atmosphere; and
[0047] d') optionally processing the solid material obtained in step c') to a desired particle size distribution.
[0048] The invention furthermore relates to a solid material obtainable by said second process.
[0049] The present invention also relates to a solid material having the following general formula (I):
[0050] Li 6-x-2y Cu x PS 5-y X (I)
[0051] in:
[0052] -X is selected from the group consisting of: F, Cl, I and Br;
[0053] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0054] -0≤y≤0.5, preferably 0≤y≤0.25;
[0055] Use as solid electrolyte.
[0056] The present invention also relates to a solid electrolyte, which comprises at least a solid material having the following formula (I):
[0057] Li 6-x-2y Cu x PS 5-y X (I)
[0058] in:
[0059] -X is selected from the group consisting of: F, Cl, I and Br;
[0060] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0061] -0≤y≤0.5, preferably 0≤y≤0.25.
[0062] The present invention also relates to an electrochemical device, which comprises at least a solid electrolyte, wherein the solid electrolyte comprises at least a solid material having the following formula (I):
[0063] Li 6-x-2y Cu x PS 5-y X (I)
[0064] in:
[0065] -X is selected from the group consisting of: F, Cl, I and Br;
[0066] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0067] -0≤y≤0.5, preferably 0≤y≤0.25.
[0068] The present invention also relates to a solid-state battery, which comprises at least a solid electrolyte, and the solid electrolyte comprises at least a solid material having the following formula (I):
[0069] Li 6-x-2y Cu x PS 5-y X (I)
[0070] in:
[0071] -X is selected from the group consisting of: F, Cl, I and Br;
[0072] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0073] -0≤y≤0.5, preferably 0≤y≤0.25.
[0074] The present invention also relates to a vehicle, which comprises at least a solid-state battery, which comprises at least a solid electrolyte, and the solid electrolyte comprises at least a solid material having the following formula (I):
[0075] Li 6-x-2y Cu x PS 5-y X (I)
[0076] in:
[0077] -X is selected from the group consisting of: F, Cl, I and Br;
[0078] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0079] -0≤y≤0.5, preferably 0≤y≤0.25.
[0080] definition
[0081] Throughout this specification, unless the context dictates otherwise, the words "comprise" or "include" or variations such as "comprises", "comprising", "includes", "including", will be understood to mean the inclusion of the stated elements or method steps or groups of elements or method steps but not the exclusion of any other elements or method steps or groups of elements or method steps. According to a preferred embodiment, the words "comprise" and "include" and variations thereof mean "consisting only of".
[0082] Unless the context clearly indicates otherwise, as used in this specification, the singular forms "a / an" and "the" include plural forms. The term "and / or" includes the meanings of "and", "or" and also includes all other possible combinations of the elements connected with the term.
[0083] The term "between" should be understood to include the limit values.
[0084] Ratios, concentrations, amounts, and other numerical data may be expressed in range form herein. It should be understood that this range form is used only for convenience and brevity and should be flexibly understood to include not only the numerical values explicitly stated at the limits of the range, but also all single numerical values or sub-ranges encompassed within the range, just as each numerical value and sub-range are explicitly stated. For example, a temperature range of about 120°C to about 150°C should be understood to include not only the explicitly stated limits of about 120°C to about 150°C, but also sub-ranges, such as 125°C to 145°C, 130°C to 150°C, etc., and a single amount within the specified range, including small quantities, such as, for example, 122.2°C, 140.6°C, and 141.3°C.
[0085] The term "electrolyte" refers in particular to the electrolyte that allows ions (e.g. Li + ) migrate through a material but does not allow electrons to conduct through it. Electrolytes can be used to electrically isolate the cathode and anode of a battery while allowing ions (such as Li + ) is transported through the electrolyte. A "solid electrolyte" according to the present invention is particularly intended to mean any kind of material in which ions (e.g. Li + ) can move around while the material is in a solid state.
[0086] As used herein, the term "argyrodite" or "argyrodite crystal" refers to a crystal structure or crystal bonding arrangement. This crystal structure or bonding arrangement is based on the crystal structure of the natural mineral argyrodite, which is characterized by the chemical formula Ag 8 G JZ 6 This crystal structure is also known as the isomorphous argyrodite mineral Ag. 8 S N 6 Let me give you an example.
[0087] As used herein, the term "crystalline phase" refers to a portion of a material that exhibits crystalline characteristics, for example, well-defined x-ray diffraction peaks as measured by x-ray diffraction (XRD).
[0088] As used herein, the term "peak" refers to the position on the x-axis of an XRD powder pattern with intensity versus degree (2θ) and whose peak intensity is much higher than the background. In a series of XRD powder pattern peaks, the main peak is the peak with the highest intensity, which is related to the compound or phase being analyzed. The second main peak is the peak with the second highest intensity. The third main peak is the peak with the third highest intensity.
[0089] The term "electrochemical device" refers in particular to a device that generates and / or stores electrical energy, for example by electrochemical and / or electrostatic methods. An electrochemical device may include an electrochemical cell such as a battery, notably a solid-state battery. The battery may be a primary (i.e., single or "disposable") battery, or a secondary (i.e., rechargeable) battery.
[0090] As used herein, the terms "cathode" and "anode" refer to the electrodes of a battery. During the charge cycle of a Li-secondary battery, Li ions leave the cathode and move through the electrolyte and reach the anode. During the charge cycle, electrons leave the cathode and move to the anode through an external circuit. During the discharge cycle of a Li-secondary battery, Li ions pass through the electrolyte and migrate from the anode to the cathode. During the discharge cycle, electrons leave the anode and move to the cathode through an external circuit.
[0091] It should be understood that the term "vehicle" or "vehicular" or other similar terms as used herein include general motor vehicles such as passenger cars (including sports utility vehicles (SUVs), buses, trucks, various commercial vehicles), watercraft (including various ships and vessels), aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid electric vehicles, hydrogen-powered vehicles, and other alternative fuel vehicles (e.g., fuels derived from resources other than petroleum). As mentioned herein, a hybrid vehicle is a vehicle with two or more different power sources, such as both gasoline-powered and electric vehicles. DETAILED DESCRIPTION
[0092] The present invention then relates to a solid material according to the general formula (I)
[0093] Li 6-x-2y Cu x PS 5-y XX(I)
[0094] in:
[0095] -X is halogen, preferably selected from the group consisting of: F, Cl, I and Br;
[0096] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0097] -0≤y≤0.5, preferably 0≤y≤0.25.
[0098] The solid material of the present invention is neutrally charged. It should be understood that formula (I) is an empirical formula (general formula) determined by elemental analysis. Therefore, formula (I) defines a composition that is an average of all phases present in the solid material.
[0099] X is preferably C1 and preferably 0.02≤x≤0.8, more preferably 0.03≤x≤0.6, especially 0.03≤x≤0.06. More preferably x is 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 and 0.1 or any range consisting of these values. More preferably y is 0, 0.1, 0.2, 0.3, 0.4 and 0.5, any range consisting of these values.
[0100] The solid material of the invention may be amorphous (glass) and / or crystalline (glass ceramic). Only part of the solid material may be crystalline. The crystalline part of the solid material may comprise only one crystal structure or may comprise a plurality of crystal structures. The crystallinity of the solid material (the crystallinity of the crystal structure whose ionic conductivity is higher than that of the amorphous body) is preferably comprised between 80% and 100%.
[0101] Crystallinity can be measured by NMR spectroscopy. Specifically, the solid 31 P-NMR spectrum, and for the obtained spectrum, the resonance line observed at 70 to 120 ppm was separated into Gaussian curves by using a nonlinear least square method, and the area ratio of each curve was obtained.
[0102] The solid material of the present invention preferably comprises a fraction consisting of crystalline phases, wherein one of the crystalline phases has an argyrodite structure. Preferably, the crystalline phase having an argyrodite phase accounts for from 90% to 100% of the total weight of the fraction consisting of crystalline phases. Such a fraction can be measured by X-ray diffraction by performing a Rietveld refinement on the total diffraction pattern. Such refinement can be performed with the FullProf software by using the multiphase refinement option.
[0103] The solid material of the present invention may include a structural unit PS 4 3- and structural unit PO 4 3- , wherein preferably the structural unit PS 4 3- The amount and structural unit PO 4 3- The ratio between the amounts ranges from 1000:1 to 9:1.
[0104] The solid material of the present invention may include at least peaks at 15.65°+ / -0.5°, 25.53°+ / -0.5°, 30.16°+ / -0.5°, and 31.52°+ / -0.5° (2θ) when analyzed by x-ray diffraction at 25°C using CuKα radiation.
[0105] The crystallographic space group of the solid material of the present invention is preferably the space group In this space group, the unit cell parameters of the solid materials of the present invention may be in the range of from 9,680 angstroms to 9,840 angstroms as measured by x-ray diffraction using CuKα radiation at 25°C, and further calculated using refinement methods (such as Rietveld and Le Bail refinements) with dedicated software (such as Fullprof software).
[0106] Preferably, the solid material having formula (I) according to the present invention may be as follows:
[0107]
[0108]
[0109] The composition of the compounds of formula (I) can notably be determined by chemical analysis using techniques well known to the skilled person such as, for example, X-ray diffraction (XRD) and inductively coupled plasma-mass spectrometry (ICP-MS).
[0110] The solid material of the present invention may be in the form of a powder, the D50 of which particle size distribution is preferably comprised between 0.05 μm and 10 μm. The particle size may be assessed by SEM image analysis or laser diffraction analysis.
[0111] D50 has the usual meaning used in the field of particle size distribution. Dn corresponds to the particle diameter at which n% of the particles have a diameter less than Dn. D50 (median) is defined as the size value corresponding to 50% of the cumulative distribution. These parameters are usually determined by the volume distribution of the diameter of a dispersion of solid material particles in a solution obtained with a laser diffractometer, using a standard procedure predetermined by the instrument software. The laser diffractometer uses the technique of laser diffraction to measure the size of the particles by measuring the intensity of the diffracted light when the laser beam passes through a dispersed particulate sample. The laser diffractometer can be, for example, a Mastersizer 3000 manufactured by Malvern.
[0112] D50 may notably be measured after sonication. Sonication may comprise inserting an ultrasonic probe into a dispersion of the solid material in solution and subjecting the dispersion to sonication.
[0113] The invention also relates to a method for producing a solid material according to general formula (I), which method comprises at least introducing at least lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound, optionally in one or more solvents. One or more lithium sulfide, phosphorus sulfide, halogen compound and copper compound can be used.
[0114] Notably, the present invention also relates to a method for producing a solid material according to general formula (I), the method comprising at least reacting at least lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound, optionally in one or more solvents. One or more lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound can be used.
[0115] The solid material of the present invention can be produced by any method known in the prior art for producing sulfide-based glassy solid electrolytes, such as, for example, melt extraction, full solution, mechanical grinding or slurry methods, in which the raw materials are reacted optionally in one or more solvents.
[0116] The present invention then relates to a process for preparing a solid material according to the general formula (I), said process comprising at least the following process steps:
[0117] a) obtaining a composition by mixing stoichiometric amounts of lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound, optionally in one or more solvents, under an inert atmosphere;
[0118] b) subjecting the composition obtained in step a) to a mechanical treatment;
[0119] c) optionally removing at least a portion of the one or more solvents from the composition obtained in step b) so as to obtain a solid residue;
[0120] d) heating the resulting residue obtained in step c) at a temperature ranging from 100° C. to 700° C. under an inert atmosphere, thereby forming the solid material; and
[0121] e) optionally processing the solid material obtained in step d) to a desired particle size distribution.
[0122] An inert atmosphere as used in step a) refers to the use of an inert gas; that is, a gas that does not undergo harmful chemical reactions under the reaction conditions. Inert gases are generally used to avoid unwanted chemical reactions, such as oxidation and hydrolysis reactions with oxygen and moisture in the air. Thus, an inert gas means a gas that does not chemically react with other reagents present in a particular chemical reaction. In the context of the present disclosure, the term "inert gas" means a gas that does not react with the solid material precursor. Examples of "inert gases" include, but are not limited to, nitrogen, helium, argon, carbon dioxide, neon, xenon, H 2 S.O. 2, which has less than 1000 ppm of water in liquid and gaseous form, including condensation. The gas may also be pressurized.
[0123] It is preferred to stir the raw materials while contacting each other under an inert gas (such as nitrogen or argon) atmosphere. The dew point of the inert gas is preferably -20°C or lower, particularly preferably -40°C or lower. The pressure may be from 0.0001 Pa to 100 MPa, preferably from 0.001 Pa to 20 MPa, preferably from 0.01 Pa to 0.5 MPa.
[0124] Preferably in step a), the inert atmosphere comprises an inert gas such as H 2 S, dry N 2 , dry argon or dry air (dry may mean that the gas has less than 800 ppm of water in liquid and gaseous form, including condensation).
[0125] When producing solid materials, the composition ratio of each element can be controlled by adjusting the amount of raw material compounds. The precursors and their molar ratios are selected according to the target stoichiometry. The target stoichiometry defines the ratio between the elements Li, Cu, P, S and M that can be obtained from the amount of applied precursors under complete conversion conditions without side reactions and other losses.
[0126] Lithium sulfide refers to a compound comprising: one or more sulfur atoms and one or more lithium atoms, or alternatively, one or more sulfur-containing ionic groups and one or more lithium-containing ionic groups. In certain preferred aspects, lithium sulfide may consist of sulfur atoms and lithium atoms. Preferably, lithium sulfide is Li 2 S.
[0127] Phosphorus sulfide refers to a compound comprising one or more sulfur atoms and one or more phosphorus atoms, or alternatively, one or more sulfur-containing ionic groups and one or more phosphorus-containing ionic groups. In certain preferred aspects, phosphorus sulfide can be composed of sulfur atoms and phosphorus atoms. Non-limiting exemplary phosphorus sulfides may include, but are not limited to, P 2 S 5 , P 4 S 3 , P 4 S 10 , P 4 S 4 , P 4 S 5 , P 4 S 6 , P 4 S 7 , P 4 S 8 and P 4 S 9.
[0128] Halogen compounds refer to compounds including one or more halogen atoms (such as F, Cl, Br or I) that are connected to other atoms of the compound by chemical bonds (e.g., ionic bonds or covalent bonds). In a preferred aspect, the halogen compound may include one or more of F, Cl, Br, I or a combination thereof, and one or more metal atoms. In other preferred aspects, the halogen compound may include one or more of F, Cl, Br, I or a combination thereof, and one or more non-metal atoms. Non-limiting examples may suitably include metal halides such as LiF, LiBr, LiCl, LiI, NaF, NaBr, NaCl, NaI, KaF, KBr, KCl, KI, etc. In a preferred aspect, the halogen compound suitable for use in a solid electrolyte for an all-solid lithium ion battery may include one or more halogen atoms and Li. Preferably, the halogen compound may be selected from the group consisting of: lithium bromide (LiBr), lithium chloride (LiCl), lithium iodide (LiI) and a combination thereof.
[0129] A copper compound refers to a compound comprising one or more Cu atoms bonded to other atoms of the compound by chemical bonds (e.g., ionic bonds or covalent bonds). In another aspect, the copper compound may be metallic copper. In a preferred aspect, the copper compound may include one or more Cu atoms, one or more non-metallic atoms, such as S, Cl or Br. The copper compound is preferably selected from the group consisting of CuS, Cu 2 S, Cu 2-x S (where x is comprised between 0 and 1, in particular x = 0.06 (chalcocite), x = 0.1, x = 0.2 (chalcocite)) and CuCl 2 The copper compound of the present invention may also be a mixture of metallic copper and elemental sulfur.
[0130] Preferably, the solid material of the present invention is prepared by using at least the following precursors: Li 2 S.P. 2 S 5 , LiCl and Cu 2 S. Lithium sulfide is Li 2 S, phosphorus sulfide is P 2 S 5 , the halogen compound is LiCl, and the copper compound is Cu 2 S.
[0131] Preferably, the lithium sulfide, phosphorus sulfide, halogen compound and copper compound have an average particle size comprised between 0.5 μm and 400 μm. The particle size can be evaluated by SEM image analysis or laser diffraction analysis.
[0132] The solvent may be suitably selected from one or more of polar or non-polar solvents that can substantially dissolve at least one compound selected from the group consisting of lithium sulfide, phosphorus sulfide, halogen compounds, and copper compounds. The solvent may also substantially suspend, dissolve, or otherwise mix the above components, for example, lithium sulfide, phosphorus sulfide, halogen compounds, and copper compounds.
[0133] The solvent according to the invention then constitutes the continuous phase of the dispersion with one or more of the abovementioned components in step a).
[0134] Depending on the components and the solvent, some components are then fairly dissolved, partially dissolved, or in the form of a slurry (ie, one or more components are not dissolved and then slurried with the solvent).
[0135] In a preferred aspect, the solvent may suitably be a polar solvent. The solvent is preferably a polar solvent, which is preferably selected from the group consisting of: an alkanol, especially having 1 to 6 carbon atoms, such as methanol, ethanol, propanol and butanol; a carbonate, such as dimethyl carbonate; an acetate, such as ethyl acetate; an ether, such as dimethyl ether; an organic nitrile, such as acetonitrile; an aliphatic hydrocarbon, such as hexane, pentane, 2-ethylhexane, heptane, decane and cyclohexane; and an aromatic hydrocarbon, such as tetrahydrofuran, xylene and toluene.
[0136] It should be understood that "solvent" mentioned herein includes one or more mixed solvents.
[0137] Based on the total weight of the powder mixture and the solvent, the powder mixture in an amount of about 1wt% to 80wt% and the solvent in an amount of about 20wt% to 99wt% can be mixed. Preferably, based on the total weight of the powder mixture and the solvent, the powder mixture in an amount of about 25wt% to 75wt% and the solvent in an amount of 25wt% to 75wt% can be mixed. In particular, based on the total weight of the powder mixture and the solvent, the powder mixture in an amount of about 40wt% to 60wt% and the solvent in an amount of about 40wt% to 60wt% can be mixed.
[0138] In the presence of a solvent, the temperature of step a) is preferably between the melting temperature of the chosen solvent and the boiling temperature of the chosen solvent, at a temperature at which there is no unwanted reactivity between the solvent and the mixed compounds. Preferably, step a) is carried out at between -20°C and 40°C and more preferably between 15°C and 40°C. In the absence of a solvent, step a) is carried out at a temperature between -20°C and 200°C and preferably between 15°C and 40°C.
[0139] The duration of step a) is preferably between 1 minute and 1 hour.
[0140] The mechanical treatment of the composition in step b) can be carried out by wet or dry grinding; notably by adding the powder mixture to a solvent and then grinding at about 100 to 1000 rpm, notably for a duration of from 10 minutes to 80 hours, more preferably about 4 to 40 hours.
[0141] Such milling is also referred to as reactive milling in conventional argyrodite synthesis.
[0142] Mechanical grinding also has the advantage that pulverization occurs while the glass mixture is being produced. In mechanical grinding, various methods can be used, such as rotary ball mills, tumbling ball mills, vibrating ball mills, and planetary ball mills. Mechanical grinding can be performed with or without the use of balls such as ZrO 2 is carried out under the circumstances.
[0143] Under such conditions, lithium sulfide, phosphorus sulfide, the halogen compound, and the copper compound are allowed to react in the solvent for a predetermined period of time.
[0144] In the presence of a solvent, the temperature of step b) is between the melting temperature of the chosen solvent and the boiling temperature of the chosen solvent, at a temperature at which there is no unwanted reactivity between the solvent and the compound. Preferably, step b) is carried out at a temperature between -20°C and 80°C and more preferably between 15°C and 40°C. In the absence of a solvent, step a) is carried out between -20°C and 200°C and preferably between 15°C and 40°C.
[0145] The mechanical treatment of the composition in step b) can also be carried out by stirring, notably by using techniques well known in the art, such as by using a standard powder or paste mixer.
[0146] Typically, a paste or a blend of a paste and a liquid solvent is obtained at the end of step b).
[0147] In step c), removing at least a portion of the solvent notably means removing at least about 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95% or 100% of the total weight of the solvent used, or any range included between these values. Solvent removal can be performed by known methods used in the art, such as decantation, filtration, centrifugation, drying or a combination thereof.
[0148] The temperature in step c) is chosen to allow removal of the solvent. Preferably, when drying is chosen as method for solvent removal, the temperature is chosen below boiling temperature and as a function of the vapor partial pressure of the chosen solvent.
[0149] The duration of step c) is between 1 second and 100 hours, preferably between 1 hour and 20 hours.Such a low duration can be obtained, for example, by using flash evaporation, such as by spray drying.
[0150] Preferably, step c) is carried out under an inert gas atmosphere such as nitrogen or argon. The dew point of the inert gas is preferably -20°C or lower, particularly preferably -40°C or lower. The pressure may be from 0.0001Pa to 100MPa, preferably from 0.001Pa to 20MPa, preferably from 0.01Pa to 20MPa. Notably, the pressure may be in the range of from 0.0001Pa to 0.001Pa, notably by using ultra-vacuum technology. Notably, by using primary vacuum technology, the pressure may be in the range of from 0.01Pa to 0.1MPa.
[0151] In step d), heating or heat treatment may notably allow the amorphized powder mixture obtained above (glass) to be transformed into a solid material crystal or a mixture of glass and crystal (glass ceramic).
[0152] The heat treatment is carried out at a temperature ranging from 100° C. to 700° C., preferably from 250° C. to 600° C., notably for a duration of 1 minute to 100 hours, preferably from 30 minutes to 20 hours. The heat treatment can be started directly at high temperature or by increasing the temperature at a rate comprised between 1° C. / min and 20° C. / min. The heat treatment can be completed by air quenching, or by natural cooling from the heating temperature, or by controlled temperature increase at a rate comprised between 1° C. / min and 20° C. / min.
[0153] Preferably in step d), the inert atmosphere comprises an inert gas such as dry N 2 , or dry argon (dry may mean that the gas has less than 800 ppm of water in liquid and gaseous form, including condensation). Preferably in step d), the inert atmosphere is a protective gas atmosphere, which is used in order to minimize, preferably exclude, the ingress of oxygen and moisture.
[0154] The pressure during heating may be at normal pressure or at reduced pressure. The atmosphere may be an inert gas such as nitrogen and argon. The dew point of the inert gas is preferably -20°C or lower, with -40°C or lower being particularly preferred. The pressure may be from 0.0001Pa to 100MPa, preferably from 0.001Pa to 20MPa, preferably from 0.01Pa to 20MPa. Notably, the pressure may be in the range of from 0.0001Pa to 0.001Pa, notably by using ultra-vacuum technology. Notably, by using primary vacuum technology, the pressure may be in the range of from 0.01Pa to 0.1MPa.
[0155] In step e), the solid material can be processed into a desired particle size distribution. If necessary, the solid material obtained by the method according to the invention as described above is ground (e.g., milled) into a powder. Preferably, the powder has a particle size distribution D50 value of less than 100 μm, more preferably less than 10 μm, most preferably less than 5 μm, as determined by dynamic light scattering or image analysis.
[0156] Preferably, the powder has a particle size distribution D90 value of less than 100 μm, more preferably less than 10 μm, most preferably less than 5 μm as determined by dynamic light scattering or image analysis. Notably, the powder has a particle size distribution D90 value comprised between 1 μm and 100 μm.
[0157] The present invention then also relates to a process for preparing a solid material according to the general formula (I), said process comprising at least the following process steps:
[0158] a′) obtaining a solution by mixing stoichiometric amounts of a lithium compound, a sulfide compound, a phosphorus compound, a halogen compound and a copper compound in one or more solvents under an inert atmosphere;
[0159] b') removing at least a part of the one or more solvents from the composition obtained in step a') so as to obtain a solid material;
[0160] c') heating the solid material as obtained in step b') at a temperature ranging from 100°C to 700°C, optionally under an inert atmosphere; and
[0161] d') optionally processing the solid material obtained in step c') to a desired particle size distribution.
[0162] Various features of step a') are substantially similar to those of step a), such as for example with respect to precursors and solvents.Preferably, the temperature in step a) is in the range from -200°C to 100°C, preferably from -200°C to 10°C.
[0163] The features of the solvent removal as mentioned in step b') may be similar to those described in step c). Preferably, in step b'), the temperature is in the range from 30°C to 200°C, under an inert atmosphere, and preferably at a pressure of 0.0001 Pa to 100 MPa.
[0164] The heating of step c') can be carried out under the characteristics as described in step d), preferably at a temperature ranging from 100 to 700°C, under an inert atmosphere and preferably at a pressure of 0.0001 Pa to 100 MPa.
[0165] The features of treating the solid material as mentioned in step d') may be similar to those described in step e).
[0166] The present invention also relates to a solid material having the formula (I) as a solid electrolyte, and a solid electrolyte comprising at least the solid material having the formula (I).
[0167] The solid electrolyte comprises at least a solid material having formula (I) and optionally other solid electrolytes, such as lithium argyrodite, lithium thiophosphate (such as glass or glass ceramic Li 3 PS 4 , Li 7 PS 11 ), and lithium conductive oxides such as lithium-filled garnet Li 7 La 3 Zr 2 O 12 (LLZO), sulfide.
[0168] The solid electrolyte may also optionally contain a polymer such as styrene butadiene rubber, an organic or inorganic stabilizer such as SiO 2 or dispersant.
[0169] The present invention also relates to an electrochemical device comprising a solid electrolyte, wherein the solid electrolyte contains at least a solid material having formula (I).
[0170] Preferably, in an electrochemical device, in particular a rechargeable electrochemical device, the solid electrolyte is a component of a solid structure of the electrochemical device selected from the group consisting of a cathode, an anode and a separator.
[0171] Herein, preferably, the solid electrolyte is a component of a solid structure of an electrochemical device, wherein the solid structure is selected from the group consisting of a cathode, an anode and a separator. Therefore, the solid material according to the present invention can be used alone or in combination with other components to produce a solid structure of an electrochemical device, such as a cathode, an anode or a separator.
[0172] The electrode that presents a net negative charge during discharge is called the anode and the electrode that presents a net positive charge during discharge is called the cathode. In an electrochemical device, a separator electrically isolates the cathode and anode from each other.
[0173] Suitable electrochemically active cathode materials and suitable electrochemically active anode materials are well known in the art. In the electrochemical device according to the present invention, the anode preferably comprises graphite carbon, metallic lithium, a silicon compound (such as Si, SiO x ), lithium titanate (such as Li 4 Ti 5 O 12) or a metal alloy containing lithium as an anode active material (such as Sn).
[0174] In the electrochemical device according to the present invention, the cathode preferably contains a metal chalcogenide having the formula LiMQ 2 , where M is at least one metal selected from transition metals (such as Co, Ni, Fe, Mn, Cr, and V), and Q is a chalcogen element such as O or S. Among these, a lithium-based composite metal oxide having the formula LiMO 2 is preferably used, where M is as defined above. Preferred examples thereof may include LiCoO 2 , LiNiO 2 , LiNi x Co 1-x O 2 (0 < x < 1) and spinel-structured LiMn 2 O 4 . Another preferred example thereof may include a lithium-nickel-manganese-cobalt-based metal oxide having the formula LiNi x Mn y Co z O 2 (x + y + z = 1, referred to as NMC), such as LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 , LiNi 0.6 Mn 0.2 Co 0.2 O 2 , and a lithium-nickel-cobalt-aluminum-based metal oxide having the formula LiNi x Co y Al z O 2 (x + y + z = 1, referred to as NCA), such as LiNi 0.8 Co 0.15 Al 0.05 O 2 . The cathode may contain a lithiated or partially lithiated transition metal oxyanion-based material, such as LiFePO 4 .
[0175] For example, the electrochemical device has a shape similar to a cylindrical or prismatic shape. The electrochemical device may include a housing, which may be made of steel or aluminum or a multilayer film polymer / metal foil.
[0176] Another aspect of the present invention relates to a battery, more preferably an alkali metal battery, and particularly to a lithium battery including at least one electrochemical device of the present invention (for example, two or more). The electrochemical devices may be combined with each other in the alkali metal battery of the present invention, for example, in series or in parallel.
[0177] The present invention also relates to a solid-state battery, comprising a solid electrolyte, wherein the solid electrolyte contains at least a solid material having formula (I).
[0178] Typically, a lithium solid-state battery includes a positive electrode active material layer containing a positive electrode active material, a negative electrode active material layer containing a negative electrode active material, and a solid electrolyte layer formed between the positive electrode active material layer and the negative electrode active material layer. At least one of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer contains a solid electrolyte as defined above.
[0179] The cathode of an all-solid-state electrochemical device usually contains, in addition to the active cathode material, a solid electrolyte as a further component. Furthermore, the anode of an all-solid-state electrochemical device usually contains, in addition to the active anode material, a solid electrolyte as a further component.
[0180] The form of the solid structure of an electrochemical device, in particular an all-solid-state lithium battery, depends in particular on the form of the electrochemical device itself to be produced. The present invention further provides a solid structure for an electrochemical device, wherein the solid structure is selected from the group consisting of a cathode, an anode and a separator, wherein the solid structure for an electrochemical device comprises a solid material according to the present invention.
[0181] Multiple electrochemical cells can be combined into an all-solid-state battery, which has both solid electrodes and a solid electrolyte.
[0182] The solid materials disclosed above can be used to prepare electrodes. The electrodes can be positive electrodes or negative electrodes.
[0183] The electrodes typically comprise at least:
[0184] -Metal substrate;
[0185] - at least one layer directly adhered to said metal substrate, said layer being made of a composition comprising:
[0186] (i) a solid material having the following formula (I):
[0187] Li 6-x-2y Cu x PS 5-y X (I)
[0188] in:
[0189] -X is selected from the group consisting of: F, Cl, I and Br;
[0190] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0191] -0 ≤ y ≤ 0.5, preferably 0 ≤ y ≤ 0.25;
[0192] (ii) at least one electroactive compound (EAC);
[0193] (iii) optionally at least one lithium ion conducting material (LiCM) other than the solid material of the present invention;
[0194] (iv) optionally at least one electrically conductive material (ECM);
[0195] (v) optionally a lithium salt (LIS);
[0196] (vi) optionally at least one polymeric binder material (P).
[0197] An electroactive compound (EAC) refers to a compound that can bind to or insert into the structure of an electrochemical device and release lithium ions during the charging and discharging stages of the electrochemical device. The EAC can be a compound capable of intercalating and deintercalating lithium ions in the structure of the electrochemical device. For the positive electrode, the EAC can be a composite metal chalcogenide having the formula LiMeQ 2 where:
[0198] - Me is at least one metal selected from the group consisting of Co, Ni, Fe, Mn, Cr, Al, and V;
[0199] - Q is a chalcogen element, such as O or S.
[0200] More particularly, the EAC can have the formula LiMeO 2 . Preferred examples of the EAC include LiCoO 2 , LiNiO 2 , LiMnO 2 , LiNi x Co 1-x O 2 (0 < x < 1), LiNi x Co y Mn z O 2 (0 < x, y, z < 1 and x + y + z = 1) (for example LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O 2 , LiNi 0.6 Mn 0.2 Co 0.2 O 2 , LiNi 0.8 Mn 0.1 Co 0.1 O 2 )、Li(Ni xCo y Al z ) 2 (x+y+z=1) and spinel structured LiMn 2 O 4 and Li(Ni 0.5 Mn 1.5 ) 4 .
[0201] EAC can also be a type having the formula M 1 M 2 (JO 4 ) f E 1-f A lithiated or partially lithiated transition metal oxyanion-based electroactive material, wherein:
[0202] -M 1 It is lithium, which can be occupied by M 1 Less than 20% partial substitution with another alkali metal;
[0203] -M 2 is a transition metal selected from Fe, Co, Mn, Ni or a mixture thereof having an oxidation level of +2, which may be oxidized to a level between +1 and +5 and which accounts for M 2 The metal is partially substituted with less than 35% (including 0) of one or more additional metals;
[0204] -JO 4 is any oxygen anion, wherein J is P, S, V, Si, Nb, Mo or a combination thereof;
[0205] -E is a fluoride anion, a hydroxide anion or a chloride anion;
[0206] -f is JO 4 The mole fraction of oxygen anions is generally comprised between 0.75 and 1.
[0207] The M defined above 1 M 2 (JO 4 ) f E 1-f The electroactive material is preferably phosphate based. It may exhibit an ordered or modified olivine structure.
[0208] For the cathode, EAC can also be sulfur or Li 2 S.
[0209] For the cathode, EAC can also be a conversion material, such as FeS 2 or FeF 2 or FeF 3 .
[0210] For the negative electrode, the EAC can be selected from the group consisting of graphitic carbon capable of intercalating lithium. More details of this type of EAC can be found in Carbon 2000, 38, 1031-1041. This type of EAC is typically in the form of powder, flakes, fibers or spheres (e.g. mesophase carbon microbeads).
[0211] The EAC may also be: lithium metal; lithium alloy compositions (such as those described in US 6,203,944 and WO 00 / 03444); lithium titanate, generally of the formula Li 4 Ti 5 O 12 These compounds are generally considered to be “zero strain” intercalation materials that absorb mobile ions (i.e., Li + ) have a low level of physical expansion; lithium-silicon alloys with a high Li / Si ratio (commonly referred to as lithium silicide), especially those with the formula Li 4.4 Lithium silicide of Si, and lithium-germanium alloys, including those having the formula Li 4.4 Crystalline phase of Ge. EAC may also be a composite material based on a carbonaceous material with silicon and / or silicon oxide, notably graphitic carbon / silicon and graphite / silicon oxide, wherein the graphitic carbon consists of one or several carbons capable of intercalating lithium.
[0212] The ECM is typically selected from the group consisting of a conductive carbonaceous material and a metal powder or fiber. The conductive carbonaceous material can be selected, for example, from the group consisting of carbon black, carbon nanotubes, graphite, graphene and graphite fibers and combinations thereof. Examples of carbon black include Ketjen black and acetylene black. The metal powder or fiber includes nickel and aluminum powder or fiber.
[0213] The lithium salt (LIS) may be selected from the group consisting of: LiPF 6 、Lithium bis(trifluoromethanesulfonyl)imide、Lithium bis(fluorosulfonyl)imide、LiB(C 2 O 4 ) 2 、LiAsF 6 、LiClO 4 , LiBF 4 、LiAlO 4 、LiNO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiN(SO 2 C 2 F 5 ) 2 、LiC(SO 2 CF3 ) 3 、LiN(SO 3 CF 3 ) 2 ,LiC 4 F 9 SO 3 、LiCF 3 SO 3 、LiAlCl 4 、LiSbF 6 , LiF, LiBr, LiCl, LiOH and lithium 2-trifluoromethyl-4,5-dicyanoimidazole.
[0214] The function of polymer binder (P) is to keep the components of the composition together.Polymer binder is usually inert.Preferably, it should also be chemically stable, and contribute to electronic and ion transport.Polymer binder is well known in the art.Non-limiting examples of polymer binder especially include polymer (copolymer) based on vinylidene fluoride (VDF), styrene-butadiene rubber (SBR), styrene-ethylene-butylene-styrene (SEBS), carboxymethyl cellulose (CMC), polyamide-imide (PAI), poly (tetrafluoroethylene) (PTFE) and poly (acrylonitrile) (PAN) polymer (copolymer).
[0215] The proportion of the solid material of the present invention in the composition may be between 0.1 wt% and 80 wt%, based on the total weight of the composition. In particular, this proportion may be between 1.0 wt% and 60 wt%, more particularly between 5 wt% and 30 wt%. The thickness of the electrode is not particularly limited and should be adapted to the energy and power required in the application. For example, the thickness of the electrode may be between 0.01 mm and 1,000 mm.
[0216] Inorganic material M can also be used to prepare a separator. A separator is an ion permeable membrane placed between the anode and cathode of a battery. Its function is to allow lithium ions to pass through but block electrons, and to ensure the physical separation between the electrodes.
[0217] The diaphragm of the present invention typically comprises at least:
[0218] - a solid material having the following formula (I):
[0219] Li 6-x-2y Cu x PS 5-y X (I)
[0220] in:
[0221] -X is selected from the group consisting of: F, Cl, I and Br;
[0222] -0.005≤x≤5; preferably 0.015≤x≤1.5; and
[0223] -0≤y≤0.5, preferably 0≤y≤0.25;
[0224] - optionally at least one polymeric binding material (P);
[0225] - optionally at least one metal salt, especially a lithium salt;
[0226] - Optionally at least one plasticizer.
[0227] The electrodes and separators can be prepared using methods well known to the skilled person. This typically involves mixing the components in a suitable solvent and removing the solvent. For example, the electrodes can be prepared by a method comprising the following steps:
[0228] - applying a slurry comprising the components of the composition and at least one solvent to a metal substrate;
[0229] -Remove solvent.
[0230] Common techniques known to the skilled person are the following techniques: coating and calendering, dry and wet extrusion, 3D printing, sintering of porous foams followed by impregnation. Common preparation techniques for electrodes and separators are provided in Journal of Power Sources, 2018 382, 160-175.
[0231] Electrochemical devices, notably batteries such as the solid-state batteries described herein, can be used to manufacture or operate automobiles, computers, personal digital assistants, mobile phones, watches, camcorders, digital cameras, thermometers, calculators, laptop BIOS, communication devices or remote car locks, as well as stationary applications such as energy storage devices for power plants.
[0232] Electrochemical devices, notably batteries such as solid-state batteries as described herein, can be used notably in motor vehicles, bicycles operated by electric motors, robots, aircraft (e.g. unmanned aerial vehicles including drones), ships or stationary energy storage. Preferred are mobile devices such as vehicles, for example cars, bicycles, aircraft, or water vehicles such as ships or boats. Other examples of mobile devices are those that are portable, such as computers, especially laptops, phones or power tools, for example from the construction industry, especially drills, battery-powered screwdrivers or battery-powered nailers.
[0233] Should the disclosure of any patents, patent applications, and publications incorporated herein by reference conflict with the description of the present application to the extent that it renders a term unclear, the present description shall take precedence. BRIEF DESCRIPTION OF THE DRAWINGS
[0234] Figure 1 :Li 6-x-2y Cu x PS 5-y Powder XRD patterns of Cl: Sample A: x = 0; Sample B: x = 0.03; Sample C: x = 0.06; Sample D: x = 0.3; Sample E: x = 0.6; Sample F: x = 1.5.
[0235] Figure 2 :Li 6-x-2y Cu x PS 5-y Cl (where x = 0.3 and y = 0) 31 PNMR data. Stars represent PS 4 3- Characteristics of the entity, the pentagon symbol represents P 2 S 7 4- The characteristics of the entity, and the hexagonal symbol represents the PO 4 3- Characteristics of an entity.
[0236] Figure 3 :Li 6-x-2y Cu x PS 5-y Cl (where x = 0.3 and y = 0) 7 Li NMR data.
[0237] Experimental Section
[0238] The following examples serve to illustrate the invention but are not intended to be limiting.
[0239] X-ray diffraction
[0240] The XRD diffraction patterns of the powders were obtained on an XRD goniometer with Bragg-Brentano geometry, which had a Cu X-ray tube (CuKα wavelength of ). The setup can be used in different optical configurations, i.e. with variable or fixed divergence slits, or Soller slits. It is also possible to use a filtering device on the primary side, like a monochromator or Bragg-Brentano HD optics from Panalytical. If a variable divergence slit is used; a typical illumination area is 10 mm×10 mm. The sample holder is loaded on a rotator; the rotation speed during acquisition is typically 60 rpm. With incident Bragg-Brentano HD optics, the tube setup is operated at 40 kV / 30 mA for variable slit acquisition and at 45 kV / 40 mA for fixed slit acquisition. The acquisition step is 0.017° / step. The angular range is typically 5° to 90° of 2θ or more. The total acquisition time is typically 30 min or more. The powder is covered with Kapton film to prevent reaction with air moisture.
[0241] Conductivity and electrochemical impedance spectroscopy (EIS)
[0242] Conductivity is collected on the pellets completed using the uniaxial press running at 500MPa.Measured under a load of 40MPa, and two carbon paper foils are used as the current collector in the pressure battery cell (BATTE-CELL-0067EQ-PSC-15-P) from MTI.Impedance spectrum is collected on the BiologiccVMP3 device, and temperature control is ensured by the Binder climate chamber.The duration of two hours is set so that the temperature balance between two measurements is achieved.Impedance spectrum is collected under PEIS mode, and the mode has an amplitude of 10mV and a frequency range from 1MHz to 1kHz (25 points / decade, and an average of 50 measurements / frequency points).
[0243] Solid-state NMR
[0244] Solid-state NMR spectra were recorded on a Bruker Avance 400 spectrometer equipped with a high-speed DVT4 probe. 31 P and 6 Li measurements, where the relaxation time D1 depends on the experiment (see example below). Performed in static single pulse mode 7 Li measurement with relaxation time D1 = 120 s. 31 The reference material for P NMR was 85% H 3 PO 4 , 6 The reference material for Li NMR is 5 molL -1 LiCl aqueous solution.
[0245] Example 1: Synthesis
[0246] The weighing of precursors and sample preparation were performed in an Ar-filled glove box where oxygen and moisture levels were both below 1 ppm. In a typical experiment, the target stoichiometry of Li 6-x-2y Cu x PS 5-y Cl (0.015 ≤ x ≤ 1.5 and 0 ≤ y ≤ 0.25) Use a 30 mL glass vial to weigh Li 2 S (≥99.9%, Albemarle), P 2 S 5 (≥99%, Sigma Aldrich), LiCl (≥99%, Sigma Aldrich), and Cu 2 S (≥99.5%, Alfa Aesar) (total mass 8 g). For example, for the solid material Li 5.94 Cu 0.06 PS 5 Cl (x = 0.06 and y = 0), 3.34 g of Li 2 S, 3.27 g of P 2 S 5 , 1.25 g of LiCl and 0.14 g of Cu 2 S. The precursor used here is a powder having an average particle size comprised between 10 μm and 400 μm.
[0247] The glass vial was hermetically closed, taken out of the glove box and mixed with a Turbula mixer for 20 min. The glass vial was placed in the glove box and the sample was poured into 45 mL of ZrO 2 The grinding jar contains 66.4 g of diameter ZrO 2 Ball. Then add 8g of p-xylene (≥99%, Sigma Aldrich, anhydrous) in the tank. The tank is equipped with a fluororubber seal (Viton seal) and is hermetically sealed by the Ar atmosphere in the tank. The tank is taken out of the glove box and placed in a planetary ball mill (Pluverisette 7premium line, Fritsch). The mechanical synthesis is carried out at 800rpm during 80 15min cycles. Between each cycle, the tank is cooled naturally for 30min.
[0248] After mechanical synthesis is finished, the jar is placed in a glove box. The product and the ball are placed in two 30mL glass vials (without caps), which are placed in glass tubes. The tube is closed, taken out from the glove box and placed in a glass oven B-585 from Büchi. The sample is dried under vacuum for 2h at room temperature (25°C) and then heated to 110°C for 5h to evaporate p-xylene. Thereafter, the tube is closed (inner vacuum) and placed in a glove box. The powder is sieved and separated from the grinding balls. The powder is placed in a 30mL glass vial without caps, which is placed in a glass tube. The tube is closed, taken out from the glove box and placed in a glass oven B-585 from Büchi. The sample is heated under vacuum at 150°C for 1h, then at 280°C for 1h and finally at 300°C for 12h. The tube is closed (inner vacuum) and placed in a glove box. Take out the sample from the tube and store it for further analysis.
[0249] Example 2: Features
[0250] Regardless of the composition within the selected range, powder XRD ( Figure 1 ) shows that when x≤0.06, the argyrodite phase is dominant, with a small amount of Li 2 S. No copper-containing impurities were observed from the powder XRD, even for the selected range of higher copper contents (x=1.5). Powder XRD also showed that an increase in copper content (x) reduced the Li 2 The amount of S impurities.
[0251] The unit cell parameters were calculated on a kapton-based diffraction pattern using Le Bail refinement. This was done using Fullprof software.
[0252] X Value Unit cell parameters x=0 9,857 Angstroms x=0.03 9,848 Angstroms x=0.06 9,848 Angstroms x=0.3 9,844 Angstroms x=0.6 9,831 Angstroms x=1.5 9,810 Angstroms
[0253] x=0.3 sample 31 P NMR ( Figure 2 ) confirmed that PS 4 3- Substances dominate, with trace amounts of P 2 S 7 4- and possibly a small amount of Li 3 PO 4 Impurities.
[0254] x=0.3 sample 7 Li NMR Figure 3 ) indicates the presence of a single Li environment with a shift close to 1.38 ppm, which is consistent with the Li 6 PS 5 The displacement of the Cl phase is very consistent.
[0255] Electrochemical impedance spectroscopy measurements were performed on 6 mm diameter pellets that were densified at 500 MPa. The thickness of the pellets was close to 1 mm. EIS measurements show that low copper content increases the conductivity of the material. Therefore, samples with 0.03≤x≤0.06 benefit from higher conductivity than samples with x=0. In addition, the activation energy of samples with 0.03≤x≤0.06 remains below 0.40 eV between -20°C and 60°C. For higher copper contents (x≥0.3), the conductivity decreases and the activation energy increases, as shown in the following table:
[0256]
[0257]
[0258] -%* corresponds to the proportion of the crystalline product in the total crystalline phase as measured by peak area
[0259] -Nm is not measured.
Claims
1. A solid material according to the following general formula (I): them 6-x-2y With x PS 5-y X (I) in: - X is selected from the group consisting of: F, Cl, I and Br; - 0.01 ≤ x ≤ 0.06; and - 0 ≤ y ≤ 0.5。 2. The solid material according to claim 1, wherein X is Cl.
3. The solid material according to claim 1, wherein 0 ≤ y ≤ 0.25。 4. The solid material according to any one of claims 1 to 3, wherein The degree of crystallinity of the solid material is comprised between 80% and 100%.
5. The solid material according to any one of claims 1 to 3, wherein The solid material comprises at least peaks at 15.65° + / - 0.5°, 25.53° + / - 0.5°, 30.16° + / - 0.5°, and 31.52° + / - 0.5° (2θ) when analyzed by x-ray diffraction at 25°C using CuKα radiation.
6. The solid material according to any one of claims 1 to 3, wherein The solid material is in the form of a powder with a particle size distribution D50 comprised between 0.05 µm and 10 µm.
7. A method for producing a solid material according to any one of claims 1 to 6, the method comprising at least introducing at least lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound, optionally in one or more solvents.
8. A method for preparing a solid material according to any one of claims 1 to 6, the method comprising at least the following method steps: a) obtaining a composition by mixing stoichiometric amounts of lithium sulfide, phosphorus sulfide, a halogen compound and a copper compound, optionally in one or more solvents, under an inert atmosphere; b) applying a mechanical treatment to the composition obtained in step a); c) optionally removing at least a portion of the one or more solvents from the composition obtained in step b) so as to obtain a solid residue; d) heating the resulting residue obtained in step c) at a temperature ranging from 100° C. to 700° C. under an inert atmosphere, thereby forming the solid material; and e) optionally processing the solid material obtained in step d) to a desired particle size distribution.
9. The method according to claim 8, wherein: The copper compound is selected from the group consisting of: CuS; Cu2S; Cu 2-x S, wherein x is between 0 and 1 included; and CuCl2.
10. The method according to claim 9, wherein: x = 0.06, 0.1, or 0.
2.
11. The method according to any one of claims 8 to 10, wherein: Lithium sulfide is Li2S, phosphorus sulfide is P2S5, the halogen compound is LiCl, and the copper compound is Cu2S.
12. The method according to any one of claims 8 to 10, wherein: The solvent is selected from the group consisting of: alkanols having 1 to 6 carbon atoms; carbonates; acetates; ethers; organic nitriles; aliphatic hydrocarbons; and aromatic hydrocarbons.
13. The method according to claim 12, wherein: The solvent is selected from the group consisting of methanol, ethanol, propanol, butanol, dimethyl carbonate, ethyl acetate, dimethyl ether, acetonitrile, hexane, pentane, 2-ethylhexane, heptane, decane, cyclohexane, tetrahydrofuran, xylene and toluene.
14. The method according to any one of claims 8 to 10, wherein: In step b), the mechanical treatment is carried out by wet or dry grinding.
15. A solid material readily obtainable by a method according to any one of claims 8 to 14.
16. A method for preparing a solid material according to any one of claims 1 to 6, the method comprising at least the following method steps: a') obtaining a solution by mixing stoichiometric amounts of a lithium compound, a sulfide compound, a phosphorus compound, a halogen compound and a copper compound in one or more solvents under an inert atmosphere; b') removing at least a portion of the one or more solvents from the composition obtained in step a') so as to obtain a solid material; c') heating the solid material obtained in step b') at a temperature ranging from 100°C to 700°C, optionally under an inert atmosphere; and d') optionally processing the solid material obtained in step c') to a desired particle size distribution.
17. A solid material readily obtainable by the process according to claim 16.
18. Use of a solid material having the following formula (I) as a solid electrolyte: them 6-x-2y With x PS 5-y X (I) in: - X is selected from the group consisting of: F, Cl, I and Br; - 0.01≤ x ≤ 0.06; and - 0 ≤ y ≤ 0.5。 19. The use according to claim 18, wherein 0 ≤ y ≤ 0.25。 20. A solid electrolyte comprising at least a solid material having the following formula (I): them 6-x-2y With x PS 5-y X (I) in: - X is selected from the group consisting of: F, Cl, I and Br; - 0.01 ≤ x ≤ 0.06; and - 0 ≤ y ≤ 0.5。 21. The solid electrolyte according to claim 20, wherein 0 ≤ y ≤ 0.25。 22. An electrochemical device, comprising at least a solid electrolyte, wherein the solid electrolyte comprises at least a solid material having the following formula (I): them 6-x-2y With x PS 5-y X (I) in: - X is selected from the group consisting of: F, Cl, I and Br; - 0.01 ≤ x ≤ 0.06; and - 0 ≤ y ≤ 0.5。 23. The electrochemical device according to claim 22, wherein: 0 ≤ y ≤ 0.25。 24. A solid-state battery, comprising at least a solid electrolyte, wherein the solid electrolyte comprises at least a solid material having the following formula (I): them 6-x-2y With x PS 5-y X (I) in: - X is selected from the group consisting of: F, Cl, I and Br; - 0.01 ≤ x ≤ 0.06; and - 0 ≤ y ≤ 0.5。 25. The solid-state battery according to claim 24, wherein: 0 ≤ y ≤ 0.25。 26. A vehicle, comprising at least a solid-state battery, the solid-state battery comprising at least a solid electrolyte, the solid electrolyte comprising at least a solid material having the following formula (I): them 6-x-2y With x PS 5-y X (I) in: - X is selected from the group consisting of: F, Cl, I and Br; - 0.01 ≤ x ≤ 0.06; and - 0 ≤ y ≤ 0.5。 27. The vehicle of claim 26, wherein: 0 ≤ y ≤ 0.25。 28. An electrode comprising at least: - Metal substrate; - at least one layer directly adhered to said metal substrate, said layer being made of a composition comprising: (i) a solid material having the following formula (I): them 6-x-2y With x PS 5-y X (I) in: - X is selected from the group consisting of: F, Cl, I and Br; - 0.01 ≤ x ≤ 0.06; and - 0 ≤ y ≤ 0.5; (ii) at least one electroactive compound (EAC); (iii) optionally at least one lithium ion conducting material (LiCM) other than the solid material according to any one of claims 1 to 6; (iv) optionally at least one electrically conductive material (ECM); (v) optionally a lithium salt (LIS); (vi) optionally at least one polymeric binding material (P).
29. The electrode according to claim 28, wherein 0 ≤ y ≤ 0.25。 30. A membrane comprising at least: - A solid material having the following formula (I): them 6-x-2y With x PS 5-y X (I) in: - X is selected from the group consisting of: F, Cl, I and Br; - 0.01 ≤ x ≤ 0.06; and - 0 ≤ y ≤ 0.5; - optionally at least one polymeric binding material (P); - optionally at least one metal salt; - Optionally at least one plasticizer.
31. The diaphragm according to claim 30, wherein 0 ≤ y ≤ 0.25。 32. The separator according to claim 30, wherein the metal salt is a lithium salt.
Citation Information
Patent Citations
Electrode for a lithium battery
US6203944B1
Electrode material and compositions including same
WO2000003444A1
Positive electrode mix
CN104380508A